Adoption of clinical decision support systems in a developing country: Antecedents and outcomes of physician’s threat to perceived professional autonomy - Esmaeilzadeh, Pouyan; Sambasivan, Murali; Kumar, Naresh; Nezakati, Hossein * (Elsevier, 2015)
Objective The basic objective of this research is to study the antecedents and outcomes of professional autonomy which is a central construct that affects physicians’ intention to adopt clinical decision support systems (CDSS). The antecedents are physicians’ attitude toward knowledge sharing and interactivity perception (about CDSS) and the outcomes are performance expectancy and intention to adopt CDSS. Besides, we include (1) the antecedents of attitude toward knowledge sharing—subjective norms, social factors and OCB (helping behavior) and (2) roles of physicians’ involvement in decision making, computer self-efficacy and effort expectancy in our framework.